Learning in the Community: ESL Teacher Preparation Beyond University Classrooms - He, Ye (International Journal of Research on Service-Learning in Teacher Education, 2015)
In order to meet the needs of the growing numbers of English learners (ELs) in K-12 public school settings in the US, more and more teachers have started to seek professional development opportunities to be better prepared in working with ELs and their families. While it is critical for teachers to be equipped with knowledge regarding theories on second language learning and English-as-a-Second-Language (ESL) instructional strategies, it is equally, if not more important, for teachers to be engaged in social practices involving ELs and reflect on their roles beyond content delivery. This study described a community-based tutoring project in a graduate-level ESL teacher education course. The findings of this study indicated that the ESL tutoring project enhanced teacher cultural awareness and their development of pedagogical beliefs. Implications for extending ESL teacher education to promote teacher learning in the community were also discussed. Â